Early Hearing Interventions for Children with Hearing Loss in Africa: A 21-Year Scoping Review (2004–2025) - Stavros Hatzopoulos; Ludovica Cardinali; Piotr Henryk Skarzynski; Abiodun T. Adewunmi; Giovanna Zimatore (Children)
Background: The objectives of this scoping review were (a) to identify the most recent (in a 21-year span) literature information about hearing intervention programs in Africa and (b) to provide data on the intervention practices, policies and the factors prohibiting the larger diffusion of the hearing technologies in the African states. Methods: Queries were conducted via the PubMed and Scopus databases for the time window from 2005 to 2025. The mesh terms used were “hearing aids”, “cochlear implants”, and “hearing intervention Africa”. Only research articles and review papers were considered as good candidates. The standard English language filter was not used, so as to also identify information from non-English-speaking scientific communities and groups. Results: Data from eight papers were considered, reflecting the hearing intervention practices of six African states. These reports, although integral in themselves, examine different aspects of children’s hearing identification and grouping the information was not entirely feasible. It is assumed that since there are no organized or centralized NHS programs in the African states, the primary driver of hearing identification appears to be parental vigilance. The cochlear implant intervention is not very diffused mainly due to complex economic factors of the weak African economies. Anecdotal data refer to cultural bias versus hearing intervention technology, but this information needs further elucidation. Conclusions: The information on the African programs on hearing intervention policies is quite scarce, as in the case of African NHS. Within this context, it is very important to convince audiologists and ENTs from the African localized programs to publish their data in mainstream channels so that new information can be assessed.